Harmonious Families from the Perspective of M. Quraish Shihab: Experiences of Muslim Converts in Bali, Indonesia - Sofian Syaiful Rizal (Hukum Keluarga Islam IAIN LANGSA, 2025)
A harmonious family can be understood as an ideal concept in the order of household life which is marked by the achievement of stable emotional and spiritual conditions, which include happiness, peace of mind, a sense of security, and physical and spiritual well-being for all its members. However, for converts who have just embraced Islam, the process of building a harmonious family is often faced with spiritual and cultural challenges, especially in minority environments such as Jembrana, Bali. This study aims to examine the spiritual transformation of convert couples in building a harmonious family and examine it through the perspective of M. Quraish Shihab in his work Pengantin Al-Qur'an . This study uses an empirical method with a qualitative approach. Data were collected through in-depth interviews, observations, and documentation of convert couples who have lived a family life. The results of the study indicate that the spiritual transformation of converts plays an important role in the formation of a harmonious family, marked by increased religious understanding, strengthening of Islamic commitment, and changes in behavior in household life. The principles put forward by M. Quraish Shihab, such as compassion ( mawaddah ), tranquility ( sakinah ), and mutual understanding ( rahmah ), are important foundations in this process. This study confirms that spirituality that grows gradually is able to strengthen the foundation of a harmonious family, even though it starts from a limited initial understanding of Islam.